3D measurement of the radiation distribution in a water phantom in a hadron therapy beam - Opálka, Lukáš; Breithaupt, Bernadette; Jäkel, Oliver; Martišíková, Mária (Journal of Instrumentation, 2012)
Hadron therapy is a highly precise radio-therapeutic method with many advantages especially in cases when the tumour is close to sensitive organs where standard treatments cannot be used. For reliable treatment planning it is necessary to have calculation tools for maximization of the dose delivered to the targeted tissue and minimization of the dose outside of it. While the main physical processes in material irradiated by hadron beams are known, in reality the processes involved are complex so that analytical computations are impossible. Thus, the planning tools to incorporate simplified models and numerical approximations and an experimental method for high precision verification of the models within phantoms is desired. The development of sensitive, high resolution and online methods for measurement of the radiation environment inside of the irradiated object is the aim of this work. Such measurements are made possible by the resolving power of the state-of-the-art pixel detector Timepix. This quantum counting imaging device is able to record the characteristic shapes of the particle traces including their energies deposited in the detector. All these data recorded for each event allow to estimate the particle type, its energy and direction of flight. Event-by-event analysis is done using pattern recognition of the characteristic traces. The objective of the experiment is the detection and characterization of secondary radiation generated by the primary therapeutic beams in tissue equivalent material (water). Measurements were performed inside of a water phantom irradiated by a carbon beam at the Heidelberg Ion-Beam Therapy Center (HIT).
Gesehen am 31.10.2018